No evidence for age-related alterations in the marmoset retina - Haverkamp, Silke; Reinhard, Katja; Peichl, Leo; Mietsch, Matthias (Frontiers in Neuroanatomy, 2022)
The physiological aging process of the retina is accompanied by various and sometimes extensive changes: Macular degeneration, retinopathies and glaucoma are the most common findings in the elderly and can potentially lead to irreversible visual disablements up to blindness. To study the aging process and to identify possible therapeutic targets to counteract these diseases, the use of appropriate animal models is mandatory. Besides the most commonly used rodent species, a nonhuman primate, the common marmoset (Callithrix jacchus) emerged as a promising animal model of human aging over the last years. However, the visual aging process in this species is only partially characterized, especially with regard to retinal aberrations. Therefore, we assessed here for the first time potential changes in retinal morphology of the common marmoset of different age groups. By cell type specific immunolabeling, we analyzed different cell types and distributions, potential photoreceptor and ganglion cell loss, and structural reorganization. We detected no signs of age-related differences in staining patterns or densities of various cell populations. For example, there were no signs of photoreceptor degeneration, and there was only minimal sprouting of rod bipolar cells in aged retinas. Altogether, we describe here for the first time the maintenance of a stable neuronal architecture, distribution and number of different cell populations with only mild aberrations during the aging process in the common marmoset retina. These findings are in stark contrast to previously reported findings in rodent species and humans and deserve further investigations to identify the underlying mechanisms and possible therapeutic targets.